2020
DOI: 10.1016/j.jhep.2020.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver diseases in patients with COVID-19: A retrospective study

Abstract: It was also supported by grants from ANRS (Agence Nationale de Recherche sur le Sida et les hépatites virales).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
603
8
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(655 citation statements)
references
References 9 publications
23
603
8
21
Order By: Relevance
“…2, However, Ji et al examined 202 patients with confirmed COVID-19, 37.6% of which with non-alcoholic fatty liver disease (NAFLD), and showed that elevated GGT levels portend a more severe course of the disease. 26 It remains unclear whether these laboratory test alterations are associated with a worse prognosis. In fact, the literature has shown different results.…”
Section: Covid -19 and Hepati C Inj Urymentioning
confidence: 99%
See 1 more Smart Citation
“…2, However, Ji et al examined 202 patients with confirmed COVID-19, 37.6% of which with non-alcoholic fatty liver disease (NAFLD), and showed that elevated GGT levels portend a more severe course of the disease. 26 It remains unclear whether these laboratory test alterations are associated with a worse prognosis. In fact, the literature has shown different results.…”
Section: Covid -19 and Hepati C Inj Urymentioning
confidence: 99%
“…7 Ji and colleagues showed that patients with NAFLD had a higher risk of progression to severe COVID-19 and longer viral shedding time. 26 Further research is needed to understand the impact of COVID-19 in NAFLD.…”
Section: Covid -19 and Cldmentioning
confidence: 99%
“…As previously reported, the expression of ACE2 is abundant also in the epithelia of intestine, and as there is a rich circulation of blood from the intestine to liver, the spread of the virus in the liver is expected. Reduced hepatic innate immune status could contribute to progression of COVID-19 [24][25][26].…”
Section: Pathway Analysismentioning
confidence: 99%
“…These are risk factors for NAFLD and HCC [17]. Diabetes, hypertension, and obesity associated with NAFLD are also de- A preliminary report on NAFLD in patients with CO-VID-19 calls attention to an increased risk of disease progression [6.6% (5/126) vs. 44.7% (34/76) p < 0.0001], a higher probability of abnormal liver function on admission and at discharge [70% (53/76) vs. 11.1% (14/126) p < 0.0001], and a longer time for viral clearance (17.5 ± 5.2 days vs. 12.1 ± 4.4 days p < 0.0001), when compared with non-NAFLD individuals [18]. The authors state that NAFLD patients also had a higher risk of progression to severe COVID-19 and present an increased viral clearance time.…”
Section: The Impact Of Preexisting Liver Disease On Covid-19mentioning
confidence: 99%